Clinical characteristics of COVID-19 among COVID-19 patients with and without Diabetes in the Tertiary Care Center of Birat Medical College Teaching Hospital of Morang District, Nepal - Jha, Jyotish; Rajbanshi, Manish; Lamichhane, Bishnu; Koirala, Puru; Kumar Mehta, Ram; Aryal, Richa; Sharma, Ghanashyam (Birat Journal of Health Sciences, 2024)
Introduction: The COVID-19 outbreak was declared a global “Public Health Emergency of International Concern (PHEIC)” by the World Health Organization (WHO) in 2020. The epidemiology and clinical characteristics were under investigation among chronic patients with diabetes. Objectives: This study aimed to determine the clinical characteristics of COVID-19 among COVID-19 patients with diabetes and without diabetes. Methodology: A single-centered and retrospective study was carried out among 195 consecutive COVID-19 patients. Frequencies, percentages, mean, and standard deviation were determined to describe the characteristics of participants. A Chi-square test was conducted to determine the association between an individual’s characteristics and clinical characteristics of COVID-19. All the tests were conducted at a 95% Confidence interval and p-value of less than 0.05. Results: The mean±SD age was 50.9±14.7 years of 195 participants. Among them, 32.8% of the participants were female. Almost half of the participants (51.8%) had any form of diabetes. Most of the participants (62.6%) had an abnormal body mass index (BMI) and 58.8% of the patients had at least one form of comorbidities. Clinical characteristics such as cough (OR=3.1, CI: 1.4-7.5), Chest pain (OR=3.9, CI: 2.0-7.6), Tachypnea (OR=24.0 (11.3-50.9), Tachycardia (OR=20.3, CI:10.2-30.3), loose stool (OR=4.8, CI:1.8-12.3) were significantly associated among COVID-19 patients with diabetes. Hypertension (93.3%) was the leading comorbidity among COVID-19 patients with diabetes. Conclusion: Most of the clinical characteristics of COVID-19 are common among COVID-19 patients with diabetes. The findings of this study suggest patients with comorbidities like diabetes and hypertension should be more aware to avoid infectious diseases like COVID-19.